Comparison of the pharmacokinetics of an oral extended‐release capsule formulation of carbidopa‐levodopa (IPX066) with immediate‐release carbidopa‐levodopa (Sinemet®), sustained‐release carbidopa‐levodopa (Sinemet® CR), and carbidopa‐levodopa‐entacapone (Stalevo®). (20th May 2015) - Hsu, Ann; Yao, Hsuan‐Ming; Gupta, Suneel; Modi, Nishit B.
Abstract IPX066 (extended‐release carbidopa‐levodopa [ER CD‐LD]) is an oral extended‐release capsule formulation of carbidopa and levodopa. The single‐dose pharmacokinetics of ER CD‐LD (as 2 capsules; total dose, 97.5 mg‐390 mg CD‐LD) versus immediate‐release (IR) CD‐LD (25 mg‐100 mg), sustained‐release (CR) CD‐LD (25 mg‐100 mg), and CD‐LD‐entacapone (25 mg‐100 mg‐200 mg) was evaluated in healthy subjects. Following IR dosing, LD reached peak concentrations (Cmax) at 1 hour; LD concentrations then decreased rapidly and were less than 10% of peak by 5 hours. With CR CD‐LD and CD‐LD‐entacapone, LD Cmax occurred at 1.5 hours, and concentrations were less than 10% of peak by 6.3 and 7.5 hours, respectively. The initial increase in LD concentration was similar between ER CD‐LD and IR CD‐LD and faster than for CR CD‐LD and CD‐LD‐entacapone. LD concentrations from ER CD‐LD were sustained for approximately 5 hours and did not decrease to 10% of peak until 10.1 hours. Dose‐normalized LD Cmax values for ER CD‐LD were significantly lower (P< .05) than for the other CD‐LD products. Bioavailability of LD from ER CD‐LD was 83.5%, 78.3%, and 58.8% relative to IR CD‐LD, CR CD‐LD, and CD‐LD‐entacapone, respectively.